Students’ Perception On Language Style Used By English Lecturers In The Classroom - yahmun yahmun; Susanto Susanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
The objective of the research is to analyse the students percetion on lectures language style used in daily communication. There are five types of language styles, namely frozen, formal, consultative, casual and intimate. In the world of learning, especially in tertiary institutions, the language style used by a lecturer is one of the determining factors for student success. However, the determining factor for the success of a student in learning can not only be seen from the language style of a lecturer but also from the perceptions of the students. It is because of that the authors are interested in analyzing students' perceptions of the style of language used by a lecturer in class at STKIP PGRI Trenggalek. This research is a descriptive study using a qualitative method in which the population is students majoring in English education at STKIP PGRI Trenggalek in the 2022/2023 academic year. Participants were selected using purposive sampling, while the instrument in this study was a questionnaire. The results of this study in general were that students had a pretty good perception (832.4) of the style of language used by lecturers in class with the highest score in the consultative style of 1274 and the lowest score in the intimate style of 369.